Failure Identification: Procedural Causes and Corresponding Responsibilities. Issue 3 (1st August 2017) - Brehm, Eric; Hertle, Robert
Abstract: When structural members fail, there must be a physical cause, such as missing reinforcement or failing supports. The physical cause itself is often triggered by deficits in the design, in the execution and in the chosen reliability management procedures. Consequently, these deficits determine the level of responsibility for the failure of the involved parties. Human error generally plays a major role in the development of procedural issues; thus, the focus of avoidance in a reliability management system is of special importance. This paper defines the relevant aspects of a reliability management system, introduces practical examples of failure investigations and outlines the related measures to avoid human error that may have contributed to the failure.